Growth Kinetics of Lactobacillus acidophilus, Lactiplantibacillus plantarum and Lacticaseibacillus rhamnosus under Different Cultivation Conditions - Sabrina dos Santos Rocha; Aura Lacerda Crepaldi; Ingrid Lessa Leal; Tatiana Oliveira do Vale; Antônio Carlos Freitas Souza (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Probiotics are live microorganisms that benefit the health of the host when administered in adequate amounts. Among the various microorganisms with probiotic activity, lactic acid bacteria (LAB) are commonly used for this purpose. In this perspective, we sought to evaluate the growth kinetics of strains of the species Lactobacillus acidophilus, Lactiplantibacillus plantarum, and Lacticaseibacillus rhamnosus, identifying suitable parameters for the cultivation process. The experiment was conducted with the addition of 1% inoculum in MRS broth. Microbial growth and specific rate (µspecific) were determined by measuring optical density (OD600) and cell viability on plates. Three treatments were tested (no agitation, 100, and 150 RPM) at a constant temperature of 37°C. The results obtained demonstrate that L. plantarum presented the highest specific growth rate (µspecific=0.34/h), followed by L. rhamnosus (µspecific=0.32/h) and L. acidophilus (0.19/h). We also demonstrated that all strains showed a decline in viability in the agitation treatments after 24 hours of cultivation. The kinetic values evaluated suggest that the three strains can be cultivated under static conditions for a period of 24 hours without compromising the productivity of the bioprocess in terms of cell viability.